Magnetoresistive and Magnetooptical Properties of the Film Systems with Possible Spin-Dependent Electron Scattering - I. Yu. Protsenko, I. V. Cheshko, L. V. Odnodvorets’, D. M. Kondrakhova, O. V. Pylypenko, Yu. M. Shabel’nyk, O. V. Vlasenko (Успехи физики металлов, 2013)
Experimental findings of investigation of magnetoresistive and magnetooptical properties of materials, in which the spin-dependent electron scattering can be implemented in the film magnetic Co- and Fe-based systems as well as nonmagnetic Cu-, Ag-, Au-, Cr-, Pt-, Pd-, and Ge-based ones are presented. As shown, depending on atomic solubility degree, in device systems such as multilayers, spin-valves or granular systems, the different features of remagnetization processes, magnetoresistance, and magneto-optical Kerr effect manifest themselves.